Analysis of Design Management Course in College Design Major Teaching - He, Tiantian (International Journal of Global Economics and Management, 2024)
With the rapid development of the global design industry, design management is increasingly important as a bridge between design and business. In the teaching of design major in universities, how to effectively integrate design management knowledge into teaching practice and cultivate design management talents with innovative spirit and practical ability has become an urgent problem to be solved in the field of design education. Based on the existing research, this paper further discusses the practice path of design management courses in the teaching of university design major.